Female labor force participation and fertility in the Philippines - Villa, Ruby Roque 1947-
Utilizing data from the 1973 National Demographic Survey, fertility differentials for married Filipino women were determined according to their employment status. Multiple Classification Analysis and Dummy Variable Regression were employed to determine the effect of female labor force participation on fertility singly or in combination with other variables. The thesis demonstrated that high fertility led to a withdrawal from the labor force and that female labor force participation lead to lower fertility levels thereby giving two dimensions to the role-incompatibility hypothesis. The analysis also substantiated that professionals and clerical workers had the lowest fertility levels; farm owners, farm and sales workers displayed the highest fertility levels, while skilled and service workers manifested intermediate rates. Moreover, the study verified that among class of work status groups, employees and employers had the lowest number of children ever born while unpaid family workers and the self-employed exhibited the highest fertility levels. Furthermore, the study upheld that duration of marriage is the biggest single predictor variable for fertility examined in this study. Age of wife ranked second. Among the non-demographic variables, education accounted for the highest amount of variation in fertility followed in turn by occupation and class of worker status. Residence accounted for the smallest amount of variation on fertility in the study.